DESIGN OF A WEB-BASED VILLAGE INCOME MAPPING SYSTEM USING HIERARCHICAL CLUSTERING IN CILETUH GEOPARK - Gina Raodotul Jannah; Dudih Gustian; Moneyta Dholah Rosita (Program Studi Teknik Informatika Universitas Khairun, 2025)
Cikelat Village, located within the Ciletuh–Palabuhanratu UNESCO Global Geopark, has significant potential in agriculture, MSMEs, and tourism. However, the absence of a structured information system limits the optimal utilization of these resources. This study maps the income distribution of Cikelat residents using the Hierarchical Clustering method and designs a web-based information system as a decision-support tool. Data from 438 respondents were preprocessed, normalized, and analyzed using Ward’s linkage and Euclidean distance, producing a dendrogram that identified three distinct socio-economic clusters: (1) Cluster 1 (212 respondents, 48.4%) – educated, self-employed residents with moderate income and high technology adoption; (2) Cluster 2 (131 respondents, 29.9%) – predominantly farmers with low income but positive perceptions of the Geopark’s benefits; and (3) Cluster 3 (95 respondents, 21.7%) – low-income groups with limited education and technology use. ANOVA confirmed significant differences among clusters (p < 0.05). The system design follows the waterfall model and includes class diagrams and a prototype interface developed in Figma. Although still at the design stage, the proposed system provides a practical blueprint for future implementation and supports data-driven policymaking and sustainable rural development.